2012
DOI: 10.1016/j.cell.2012.08.034
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 Is a Regulator of Adipose Oxidative Metabolism, Inflammation, and Energy Homeostasis

Abstract: Summary PGC1α is a key transcriptional coregulator of oxidative metabolism and thermogenesis. Through a high throughput chemical screen, we found that molecules antagonizing the TRPVs (Transient Receptor Potential Vanilloid), a family of ion channels, induced PGC1α expression in adipocytes. In particular, TRPV4 negatively regulated the expression of PGC1α, UCP1 and cellular respiration. Additionally, it potently controlled the expression of multiple proinflammatory genes involved in the development of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
303
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(322 citation statements)
references
References 63 publications
16
303
2
1
Order By: Relevance
“…Because we found cilia of human TM cells to respond to pressure changes, and OCRL is known to transport membrane bound proteins, we hypothesized that it may interact with a mechanosensory channel within the cilia. TRPV4 is a mechanosensitive calcium-permeable cation channel that localizes to cilia, where it functions in osmotic regulation (32,(37)(38)(39). TRPV4 dysregulation has been implicated in diseases with fluid overload, such as hydrocephalus and heart failure (32,40).…”
Section: Resultsmentioning
confidence: 99%
“…Because we found cilia of human TM cells to respond to pressure changes, and OCRL is known to transport membrane bound proteins, we hypothesized that it may interact with a mechanosensory channel within the cilia. TRPV4 is a mechanosensitive calcium-permeable cation channel that localizes to cilia, where it functions in osmotic regulation (32,(37)(38)(39). TRPV4 dysregulation has been implicated in diseases with fluid overload, such as hydrocephalus and heart failure (32,40).…”
Section: Resultsmentioning
confidence: 99%
“…4 TRPM8 stimulation by menthol increased UCP1 expression in brown adipocytes and BAT through PKA phosphorylation 5 whereas knockdown of TRPV4 facilitated UCP1 expression in 3T3-F442A adipocytes. 6 We recently reported that TRPV2 is more highly expressed in mouse brown adipocytes than TRPV1, TRPV3, TRPV4 and TRPM8. Moreover, the expression of TRPV2 was significantly increased in differentiated brown adipocytes compared with preadipocytes at mRNA, protein and functional levels.…”
mentioning
confidence: 99%
“…Recent results suggest that transient receptor potential channels may provide a novel means of indirect and direct activation of BAT-dependent thermogenesis. 74,75 As mentioned above, there are compelling data indicating that BAT thermogenesis relies on lipolysis, and that both brown and white adipocytes contribute to the total thermogenic response of lipolytic agents. In view of the failure of ADRB3 agonists to work as thermogenic agonists in humans, other means of activating lipolysis need to be exploited.…”
Section: The Central Role Of Bat In Nonshivering Thermogenesis and Tmentioning
confidence: 99%